O espaço intra e interurbano de Januária no Norte de Minas Gerais - Lara Fernanda Nunes Dourado (2020)
Cities have their spatial dynamics defined by their historical urbanization process and in function of their social, economic, political, and natural aspects, characteristic of the society in which they are inserted. They are diversified by their commercial and industrial economic potential, urban functions, demographic size, centralities and interactions with other nucleus in their urban network. In Brazil, the urban restructuring experienced after the 1970s resulted, among other effects, the minimization of the urban dysfunctions existing in the metropolises due to the disordered population and economic increase, which, consequently, highlighted the role played by small and medium cities. The magnification of research related to urban morphologies and structures at these hierarchical levels revealed that the demographic criterion is not sufficient for its recognition. Therefore, the analysis of non-metropolitan cities must also be based on intra-urban parameters, such as spatial, historical, political, social, economic aspects, morphological organization and urban centralities. On the interurban scale, researches should highlight the interactions, flows and regional roles played by these urban centers. Still about the urban studies, there is the use of models of spatial organization as an efficient methodology for analyzing the conjuncture of intra and interurban spaces, since it is recognized a pattern of ordering urban space corresponding to its hierarchical category. Therefore, this research analyzed the intra and interurban space of Januária - MG, based on the understanding of its historical, geographical and urbanization context after the 1980s, of spatial interactions and of centrality relations with its districts, municipalities in the Geographic Region Immediate and of the norte-mineira urban network to which is integrated. For it, its equipment was identified that offers of goods and services that confirmed their regional role, and still it was applied the morphological-functional zoning model for medium-sized cities in Minas Gerais, developed by Amorim Filho (2007),in order to understand the dynamics materialized in its intra-urban space. The methodological structure was based on bibliographic and documentary research, field immersion, construction of the morphological-functional cartogram of the urban space of Januária and iconographic record. The theoretical and empirical analyzes of this research recognize the Januária spatial organization initially formed due to the proximity with the São Francisco River, in which the expansion of the urban spot was driven by population growth, by urban public policies and urban equipment, after the decade of 1980.External relations of Januária reveal its centrality vis-à-vis the small municipalities of its Immediate Geographic Region and its diverse spatial interactions with the Montes Claros Intermediate Geographic Region, to which it is linked in a complementary way. The analysis of the morphological arrangement of the januarense urban nucleus was structured based on the model of Amorim Filho (2007) and made it possible to recognize Januária as a medium city “on the threshold”, in which the intra and interurban spaces are configured as a result of geographic spatial processes singular and general.